Asian perception towards bio fertilizer appliccation on paddy: a review / Normaliyana Mat Nor - Mat Nor, Normaliyana (Faculty of Plantation and Agrotechnology, 2016)
Bio fertilizer is essential component of fertilizer to increase yield of plant. It also gives positive impact to soil structure, nutrient uptake to plant and environmental friendly become produce. This review paper aims to discuss on perception people regarding to the bio fertilizer application based on Asian countries such as India, Malaysia, Vietnam, Pakistan and also Thailand. Based on the different studies done, different countries will perceive bio fertilizer application differently. Then, there are benefits of using bio fertilizer such as Blue Green Algae (BGA) inoculum, Azolla and organic matter for the growth performance production of paddy. Utilization of Azolla and organic matter give positive impacts to the plant length (cm), Green Panicle (stalk), dry weight (g), and harvest weight (ton per ha). Moreover application of Blue Green Algae (BGA) as a supplement to NPK feliilizer can enhance the production of panicle, spikes, plant height, number of grains, grain yield, and straw yield.